Morphological and Molecular Characterization of Philometroides seriolae from Japanese Amberjack Seriola quinqueradiata caught in East Sea, Republic of Korea - Choe, Seongjun; Eom, Keeseon S. (Korean journal of parasitology, 2022)
The Japanese amberjack Seriolae quinqueradiata is one of the most consumed fish species among the Koreans. However, information regarding parasitic infection in Japanese amberjack is scarce. This study described the morphological and molecular characteristics of a species of philometrid nematode, Philometroides seriolae, which was recovered from Japanese amberjack. This fish was caught in the sea of Goseong-gun, Gangwon-do, Republic of Korea (Korea). Six P. seriolae (Nematoda: Philometridae) were recovered from 2 Japanese amberjacks. These parasites were subgravid female which were 325-420 mm long and 2.95-3.27 mm wide. Furthermore, they had typical papillae distributed on their body surface with 14 papillae at the apical view. Sequence analysis of the small subunits of ribosomal RNA (SSU rRNA) showed high sequence identity (99.8%, 1,607/1,611-bp) with that of P. seriolae (GenBank accession no. FJ155811). This nematode species has been newly added to the Korean nematode fauna.